Identification of Potential Clusters of Signs and Symptoms to Prioritize Patients’ Eligibility for AADCd Screening by 3-OMD Testing: An Italian Delphi Consensus - Carlotta Spagnoli; Roberta Battini; Filippo Manti; Duccio Maria Cordelli; Andrea Pession; Melissa Bellini; Andrea Bordugo; Gaetano Cantalupo; Antonella Riva; Pasquale Striano; Marco Spada; Francesco Porta; et al. (Behavioural Neurology)
Introduction. AADCd is an ultrarare, underdiagnosed neurometabolic disorder for which a screening test (3-OMD dosing on dried blood spot (DBS)) and targeted gene therapy (authorized in the EU and the UK) are available. Therefore, it is mandatory to raise awareness of presenting symptoms and signs among practitioners. Delivering scientifically sound information to promote screening of patients with the correct cluster of symptoms and signs would be critical. Materials and Methods. In light of the lack of sound evidence on this issue, expert opinion level of evidence was elicited with the Delphi method. Fourteen steering committee members invited a panel of 29 Italian experts to express their opinions on a series of crucial but controversial topics related to using 3-OMD DBS as a screening method in AADCd. Clusters of symptoms and signs were divided into typical or atypical, depending on age groups. Inclusion in newborn screening programs and the usefulness of a clinical score were investigated. A five-point Likert scale was used to rate the level of priority attributed to each statement. Results. The following statements reached the highest priority: testing pediatric patients with hypotonia, developmental delay, movement disorders, and oculogyric crises; inclusion of 3-OMD dosing on DBS in neonatal screening programs; development of a clinical score to support patients’ selection for 3-OMD screening; among atypical phenotypes based on clinical characteristics of Italian patients: testing patients with intellectual disability and parkinsonism-dystonia. Discussion. Clusters of symptoms and signs can be used to prioritize testing with 3-OMD DBS. A clinical score was rated as highly relevant for the patient’s selection. The inclusion of 3-OMD dosing in newborn screening programs was advocated with high clinical priority.